The invasive parasitic copepod lernaea cyprinacea: Updated host-list and distribution, molecular identification and infection rates in Patagonia - Waicheim, María Agustina (2019)
Although competition and predation are mechanisms more studied in biological invasions, ecologists and conservation managers have become aware of the threat imposed by the co-introduction of parasites. Parasites can be co-introduced into new areas with a non-native host, and become co-invaders when they spill over to native hosts. The copepod Lernaea cyprinacea was presumably co-introduced to Patagonia along with the common carp, Cyprinus carpio. Our aims were to compose an updated list of the hosts of L. cyprinacea and its distribution in South America, to confirm the specific identity of Patagonian specimens using molecular tools, and to enlarge the list of hosts and localities in Patagonia, by comparing infection rates between non-native and native fishes to evaluate spillover processes. Between the years 2011 and 2017, native and non-native fish species were collected in freshwater environments from Northern Patagonia in basins where common carp and non-native fishes belonging to the Brazilian biogeographic sub-region, like Characiforms, Siluriforms, and Cyprinodontiforms, have been introduced. The sampled fishes were examined under a stereoscopic microscope to search for L. cyprinacea. At present, in South America, records of L. cyprinacea parasitizing native and non-native hosts exist for Colombia, Uruguay, Brazil, Chile and Argentina, with a total of 43 host fish species. Complete sequence data from the 18S region corroborate the identity of the Patagonian parasite based on morphological characteristics. A total of 754 fish belonging to 13 species were collected and 388 copepods were recovered. Lernaea cyprinacea was registered in almost every surveyed freshwater system in Patagonia, even in places where the original host, C. carpio, was absent. The copepod was found parasitizing two native and four non-native fish species, and in general, native fishes showed higher infection values. The present study enlarges the list of localities in Patagonia. It also provides molecular confirmation of the specific identity. In summary, our results show how an alien parasite may switch host and disperse beyond the actual distribution range of the original host. This study provides an overview of the process of colonization of L. cyprinacea in Patagonia, which represents a threat to native species due to its pathogenicity.